2021
DOI: 10.3390/antibiotics10081018
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Activated Saline Promotes Antibiotic Treatment of Systemic Methicillin-Resistant Staphylococcus aureus Infection

Abstract: Systemic infections caused by methicillin-resistant Staphylococcus aureus (MRSA) are life-threatening due to their strong multidrug resistance, especially since the biofilms formed by MRSA are more difficult to inactivate by antibiotics, causing long term recurrence of infection. Plasma-activated saline (PAS), a derived form of cold atmospheric-pressure plasma, can effectively inactivate bacteria and cancer cells and has been applied to sterilization and cancer treatment. Previous studies have demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Although it is difficult to conclude which working gas is most effective in PALs inactivation of biofilms, many studies have demonstrated that the addition of small amounts of oxygen to noble gases could enhance the antimicrobial activity of PALs, and when the ambient air is used as working gas, greater inactivation efficacy can usually be achieved as compared to noble gases (Li et al, 2015). Yang et al (2021) used synthetic air (79% N 2 + 21% O 2 )-produced plasma-activated saline (PAL) for the inactivation of methicillin-resistant S. aureus (MRSA) biofilms formed on silica films. The treatment of PALs alone achieved an approximately 1.2-log reduction of MRSA cells in the biofilm.…”
Section: Processing Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although it is difficult to conclude which working gas is most effective in PALs inactivation of biofilms, many studies have demonstrated that the addition of small amounts of oxygen to noble gases could enhance the antimicrobial activity of PALs, and when the ambient air is used as working gas, greater inactivation efficacy can usually be achieved as compared to noble gases (Li et al, 2015). Yang et al (2021) used synthetic air (79% N 2 + 21% O 2 )-produced plasma-activated saline (PAL) for the inactivation of methicillin-resistant S. aureus (MRSA) biofilms formed on silica films. The treatment of PALs alone achieved an approximately 1.2-log reduction of MRSA cells in the biofilm.…”
Section: Processing Factorsmentioning
confidence: 99%
“…In recent studies, differences in inactivation efficiency toward plasma-treated solutions in treating different types/forms of microorganisms have been reported. Many studies have used various solutions to generate PALs to investigate their inactivation efficiency toward biofilm cells, including PBS (Hong et al, 2021;İbiş & Ercan, 2020;Joshi et al, 2010;Kwandou et al, 2018;Seo et al, 2019), saline solution (0.9%) (Bhatt et al, 2018;Chen et al, 2016;Hong et al, 2021;Yang et al, 2021), NAC (İbiş & Ercan, 2020), citrate solution (Chen et al, 2016), and a number of organic solutions, including glucose, cysteine, glycine, proline, methionine, threonine, glutamate, arginine, and heparin (Ercan et al, 2014). In the study of Ercan et al (2014), it was reported that the plasma-treated methionine solution was more efficient and significant in inhibiting the biofilms of all the bacterial strains tested (carbapenem-resistant Acinetobacter baumannii, MRSA, metallo-β-lactamase (NDM1)-positive Klebsiella pneumoniae, and Enterococcus faecalis) by preventing the formation of biofilms by 70% as compared to untreated ones.…”
Section: Different Pals and Their Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In medicine, plasma has received a lot of attention as a novel tool, and the field of plasma medicine was created, and PAL is also being discussed as an aqueous plasma pharmacy as a field within plasma medicine [16,39]. In the area of PAL, in addition to the wound healing, disinfection, and cancer therapy mentioned above, active research is being conducted on making plasmaactivated oil or hydrogel [116,117], combined therapy with other treatments [123], and interaction with drugs [124].…”
Section: Futurementioning
confidence: 99%